On the Solution of a Concentrated Torque Problem for a Non-Homogeneous Orthotropic Half-Space - Rogowski, B. (Engineering Transactions, 1992)
The exact expression for displacement and stresses in a non-homogeneous orthotropic half-space subjected to a concentrated torque acting in the interior or on a surface are obtained by means of Hankel transforms.